2006
DOI: 10.1002/rmv.524
|View full text |Cite
|
Sign up to set email alerts
|

Torque teno virus (TTV): current status

Abstract: Torque teno virus (TTV), currently classified into the family Circoviridae, genus Anellovirus, was first found in a patient with non-A-E hepatitis. TTV has a single stranded circular DNA of approximately 3.8 kb. TTVs are extraordinarily diverse, spanning five groups including SANBAN and SEN viruses. Torque teno mini virus (TTMV) with approximately 2.9 kb genome also has wide variants. Recently, two related 2.2- and 2.6-kb species joined this community. Recombinations between variants are frequent. This extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
133
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(145 citation statements)
references
References 75 publications
2
133
0
7
Order By: Relevance
“…In this study, we evaluated the frequency of serum TTV DNA and their genotypes in relation to liver disease in HIV patients as well as in healthy control blood donors .The aim of this study was to investigate the prevalence of SEN-V-D/H and TTV co infection in HIV patients and healthy blood donors in southern Iran. Because of the therapeutic procedures that are frequently associated with bleeding and blood transfusions, HIV patients are at increased risk for infection with blood-borne viruses 7,15 . TTV and SEN-V were detected 34% and 37.33% of healthy blood donors respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we evaluated the frequency of serum TTV DNA and their genotypes in relation to liver disease in HIV patients as well as in healthy control blood donors .The aim of this study was to investigate the prevalence of SEN-V-D/H and TTV co infection in HIV patients and healthy blood donors in southern Iran. Because of the therapeutic procedures that are frequently associated with bleeding and blood transfusions, HIV patients are at increased risk for infection with blood-borne viruses 7,15 . TTV and SEN-V were detected 34% and 37.33% of healthy blood donors respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The genome of SEN-V is similar to TTV and both are classifi ed within the circovirus family 5 . Both SEN-V and TTV are single-stranded non-enveloped DNA viruses of 3,800 nucleotides 6,7 . Several studies have shown that in HIV-infected patients the prevalence of TTV is slightly higher compare to healthy blood donors 8 .…”
Section: Introductionmentioning
confidence: 99%
“…TTV was originally named after the initials of first patient TT, then transfusion-transmitted, and recently renamed "torque teno" virus [73]. Due to the high degree of genomic variability of the putative coding regions [74] and difficulties in expression of full-length TTV protein for antibody testing [75,76], the diagnosis of TTV infection has been dependent on PCR detection of viral DNA using primers specific for the noncoding regions [77].…”
Section: Hres-1/p28 With Viral Peptides and The 70 Kda Protein Of U1 mentioning
confidence: 99%
“…TTV is a single-stranded DNA virus, of around 3.8 Kb, distantly related to circoviruses and classified in the genus Arnellovirus (Biagini, 2009;Hino & Miyata, 2007). TTV represents in fact a swarm of viruses, which chronically infects human and other animals, and was originally thought to be associated with hepatitis.…”
Section: Other Parenterally-transmitted Viruses Historically Associatmentioning
confidence: 99%
“…One of these genogroups comprises SEN-V, another virus initially associated with hepatitis. Preliminary evidence suggests that some SENwww.intechopen.com V types may be associated to hepatitis, although this association could be a casual event, and then not meaning that SEN-V is actually a true hepatotropic virus (Hino & Miyata, 2007). …”
Section: Other Parenterally-transmitted Viruses Historically Associatmentioning
confidence: 99%